To evaluate the expression \( 2y^2 - \frac{x}{a} + 12 \) given \( x = 16 \), \( y = -6 \), and \( a = 2 \), we can follow these steps:
- Calculate \( 2y^2 \).
- Calculate \( \frac{x}{a} \).
- Combine the results with the constant 12.
Let's go step by step.
-
Calculate \( 2y^2 \): \[ y^2 = (-6)^2 = 36 \] \[ 2y^2 = 2 \times 36 = 72 \]
-
Calculate \( \frac{x}{a} \): \[ \frac{x}{a} = \frac{16}{2} = 8 \]
-
Now substitute these values back into the expression: \[ 2y^2 - \frac{x}{a} + 12 = 72 - 8 + 12 \]
-
Perform the addition and subtraction: \[ 72 - 8 = 64 \] \[ 64 + 12 = 76 \]
Thus, the value of the expression is \( \boxed{76} \).